Brentuximab vedotin prior to allogeneic stem cell transplantation in Hodgkin lymphoma: a report from the EBMT Lymphoma Working Party. (22nd February 2018) - Bazarbachi, Ali; Boumendil, Ariane; Finel, Hervé; Mohty, Mohamad; Castagna, Luca; Peggs, Karl S.; Blaise, Didier; Afanasyev, Boris; Diez‐Martin, José L.; Sierra, Jorge; Bloor, Adrian; Martinez, Carmen; et al.
Summary: Brentuximab vedotin (BV) is an anti‐CD30 antibody‐drug conjugate. Preliminary data suggest that BV might improve outcomes after allogeneic stem cell transplantation (SCT) for Hodgkin lymphoma (HL) when used as pre‐transplant salvage therapy. Between 2010 and 2014, 428 adult patients underwent an allogeneic SCT for classical HL at participating centres of the European Society for Blood and Marrow Transplantation. We compared the outcomes of 210 patients who received BV prior to allogeneic SCT with that of 218 patients who did not receive BV. The median follow‐up for survivors was 41 months. Patients in the BV group were more heavily pre‐treated (median pre‐allograft treatment lines: 4 vs. 3). The two groups were comparable in terms of disease status, performance status, comorbidities, prior autologous SCT, type of donor, conditioning and in vivo T cell depletion. In multivariate analysis, pre‐allograft BV had no impact on acute graft‐versus‐host disease (GVHD), non‐relapse mortality, cumulative incidence of relapse, progression‐free survival or overall survival (OS), but significantly reduced the risk of chronic GVHD (hazard ratio = 0·64; 95% confidence interval = 0·45–0·92; P < 0·02). Older age, poor performance status, use of pre‐transplant radiotherapy and active disease at SCT adversely affected OS. Patients allografted for HL after prior exposure to BV do not have a superior outcome after allogeneic SCT except for a lower risk of chronic GVHD. However, BV may improve the outlook of allogeneic SCT by helping otherwise refractory patients to achieve a more favourable disease status, facilitating allotransplant success.